UK Fixation of Distal Tibia Fractures (UK FixDT): protocol for a randomised controlled trial of ‘locking’ plate fixation versus intramedullary nail fixation in the treatment of adult patients with a displaced fracture of the distal tibia - Achten, Juul (BMJ Open, 2015)
INTRODUCTION: The treatment of displaced, extra-articular fractures of the distal tibia remains controversial. These injuries are difficult to manage due to limited soft tissue cover, poor vascularity of the area and proximity to the ankle joint. Surgical treatment options are expanding and include locked intramedullary nails, plate and screw fixation and external fixator systems. The nail and plate options are most commonly used in the UK, but controversy exists over which treatment is most clinically and cost-effective. In this multicentre randomised controlled trial we aim to assess ratings of disability 6 months postinjury in patients who have sustained a distal tibia fracture treated with either an intramedullary nail or plate and locking screw fixation. METHODS AND ANALYSIS: Adult patients presenting at trial centres with an acute fracture of the distal tibia will be considered for inclusion. A total of 320 patients will provide 90% power to detect a difference of 8 points in Disability Rating Index (DRI) score at 6 months at the 5% level. The randomisation sequence is stratified by trial centre and age, and administered via web-based service with 1:1 treatment allocation. Baseline demographic and pre-injury functional data and radiographs will be collected using the DRI, Olerud and Molander, and EuroQol EQ-5D questionnaire. Clinical assessment, early complications and radiographs will be recorded at 6–8 weeks. Functional outcome, health-related quality of life and resource use will be collected at 3, 6 and 12 months postoperatively. The main analysis will investigate differences in DRI 6 months postsurgery, between the two treatment groups, on an intention-to-treat basis. Tests will be two-sided and considered to provide evidence for a significant difference if p values are <0.05. ETHICS AND DISSEMINATION: NRES Committee West-Midlands, 6/11/2012 (ref:12/WM/0340). The results of the trial will be disseminated via peer-reviewed publications and presentations at relevant conferences. TRIAL REGISTRATION NUMBER: ISRCTN99771224.